Nursing Project Management to Reduce the Operating Room Infection - Yuanyuan CHEN; Xiaodao HAN; Yongjie XU; Weihua LI (Tehran University of Medical Sciences, 2017)
Background: Nursing project management is widely used in different aspects of the society. However, whether the nursing project management can control the infections in the operation room (OR) is rarely reported. We evaluated the outcomes of surgical patients after implementing a nursing project management program to provide new scientific ways to manage the OR infections. Methods: Overall, 382 patients, who underwent surgical treatment in Qilu Hospital of Shandong University, Shandong, China from May 2015 to January 2016, were enrolled as observation group. Besides, 347 cases were selected as control group. Patients in the observation group were treated with the nursing project management plan, while patients in the control group were treated with the routine operation-room nursing measures. The infection control rates in the OR, and the patient satisfaction with the nursing team postoperatively were both compared between the two groups of patients. Results: The OR air, the surgical and personnel's hands surfaces were sampled for colony forming units, and all were found to be significantly of better quality (indicated by less colony forming units) in the observation group (P<0.001). In addition, there were 3 cases (0.79%) of post-operation infections in the observation group, while 12 cases (3.46%) occurred in the control group. The overall infection rate of the observation group was significantly lower than that of the control group (P = 0.011); and the satisfaction of patients with the nursing team in the observation group was significantly higher than that of the patients in the control group (P = 0.001). Conclusion: It is worth popularizing and applying a good nursing project management plan for surgical patients in hospitals.